TUGAS GURU SEBAGAI PENGEMBANGAN KURIKULUM DI SMP S TRI BAKHTI PIR TRANS SOSA IV - atminah, tri (JURNAL NALAR PENDIDIKAN, 2019)
This research was made for teachers as curriculum developers who must be able to explain and implement the values contained in the curriculum for their students. To develop a curriculum, a teacher must achieve the following activities, namely: planning, implementing and evaluating the curriculum. Through curriculum planning, teachers can more easily achieve the goals of the learning process and can explore the potential or abilities of their students. After planning, the teacher must be able to implement the curriculum planning for students. Then after implementing the curriculum, the teacher must evaluate the curriculum used, whether the curriculum is running optimally, or vice versa. The steps that the teacher must take in teaching are preparing students, explaining the material, and evaluating students, to find out the success of teaching.Keywords: teacher, developer, curriculum